Educational Elements and Entrepreneurial Intention: The Mediating Role of Entrepreneurship Education in Higher Education - Andi Tenri Harahap; Andi Raina Ananda Herdiyana; Dea Natalia Boron (Indonesian Journal of Business and Entrepreneurship Research, 2025)
This study examines the effects of educational elements, namely entrepreneurship material, teaching methods, and the learning environment, on entrepreneurial intention through entrepreneurship education in the higher education context. A quantitative approach was employed using survey data collected from 104 respondents in higher education institutions. The analysis was conducted to evaluate both the direct effects of entrepreneurship material, teaching methods, and learning environment on entrepreneurship education and the indirect effects on entrepreneurial intention through entrepreneurship education. The findings indicate that relevant entrepreneurship material, interactive teaching methods, and a supportive learning environment significantly enhance entrepreneurship education. Furthermore, entrepreneurship education has a positive and significant effect on entrepreneurial intention and serves as an important mediating mechanism in explaining how educational elements shape entrepreneurial intention. These results suggest that entrepreneurial intention is more likely to develop when entrepreneurship learning is supported by practice-oriented content, participatory instruction, and conducive academic settings. This study highlights the importance of strengthening curriculum quality, instructional strategies, and institutional support to improve the effectiveness of entrepreneurship education in fostering entrepreneurial intention.